PENGARUH PENGEMBANGAN SDM, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KETAHANAN PANGAN KABUPATEN OKU - Pahlipi, Suri; Sari, Yunita; Oktarina, Yetty; Efrianti, Rini (Fakultas Pertanian Universitas Mataram, 2025)
This research will be conducted at the Food Security Service of OKU Regency. The sampling method in this study uses the Census technique. The census method is one of the data collection techniques in research that is carried out by taking the entire population or members of a population as a sample. In this method, each individual in the population is studied and observed thoroughly. So that from the existing population that is used as a sample / respondent based on the criteria is 40 employee respondents at the Food Security Service in OKU Regency. This data processing method aims to answer the problem formulation. To answer the problem formulation used Multiple linear regression test. The results of the study showed. HR development (X1), motivation (X2), and work discipline (X3) together have a significant effect on employee performance (Y) providing a simultaneous or joint effect of 85.3% on employee performance (Y). While the remaining 14.7% is influenced by other factors not observed in the study.